Delayed landscape responses to historical interventions: Tipu Sultan’s smelters and recent landslides - K. S. Sajinkumar (Nat Hazards, 2015)
The Western Ghats in southwest India bear testimony to frequent landslides, especially during the monsoon season, causing widespread loss of life and property. The landslides occur during the monsoon season and include debris flow, debris slide, debris avalanches, rock falls, rock slips, slumps, creeps, etc. Here, we report a finding, that requires elaborate study: a recent landslide occurred at an ancient iron ore works, but did not take place in the usual monsoon season. Such failures are concentrated in and around areas where banded iron formations (BIFs) are present. These subsurface cavities are a menace to the public, especially when construction activities are taking place.